S16-1: Evaluating GOAL!: Integrating a Physical Activity and Lifestyle Intervention Into Outpatient Care for People With Severe Mental Illness (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: People with severe mental illness (SMI) experience profound health inequalities, partly due to unhealthy lifestyle behaviours. Despite strong evidence supporting the health benefits of physical activity (PA) and other lifestyle behaviours for this population, access to integrated interventions in mental health care for people with SMI remains limited in the Netherlands. This study evaluates the implementation and (cost-)effectiveness of GOAL!, a multicomponent lifestyle programme for people with SMI in outpatient settings.Methods: GOAL! is being evaluated in a mixed-method quasi-experimental study, comparing 50 participants receiving the intervention to 50 matched individuals receiving care as usual. The intervention combines group-based and individual lifestyle coaching by a multidisciplinary team over two years. The first three months include intensive PA and nutrition support, followed by tailored and long-term guidance for sustainable behaviour change in daily life. The primary outcome is the change in PA. Secondary outcomes include other lifestyle behaviours, physical and mental health, implementation barriers and facilitators, and healthcare and societal costs.Results: Preliminary results show a promising increase in PA levels after three months (n = 55). GOAL! provides participation in 24 PA group sessions in those first three months, along with multidisciplinary collaboration with a local community sports coach and PA providers for the identification of appropriate physical activities within participants’ own living environments. Implementation facilitators at start of the programme include the high level of expected support from allied GOAL! professionals and the expected benefits of improved lifestyle, physical health, and overall wellbeing. Further results, including broader implementation outcomes and first hypotheses on cost-effectiveness, will be available in September 2025.Conclusions: GOAL! provides a programme for people with SMI in outpatient care to promote healthy lifestyle behaviours, addressing a significant service gap in the Netherlands. Early results demonstrate the feasibility and potential health benefits of this integrated approach. The findings suggest that GOAL! could effectively improve PA and overall wellbeing in this population. This case study provides valuable insights for embedding PA in mental health services across Europe, highlighting critical factors for successful implementation and potential for broader adoption.Support/Funding Source: This study is funded by the Dutch Brain Foundation (Hersenstichting) and ZonMw.Keywords: Severe mental illness, physical activity, lifestyle intervention, implementation, outpatient care